2021
DOI: 10.1186/s13690-021-00650-z
|View full text |Cite
|
Sign up to set email alerts
|

Establishing a controlled hookworm human infection (CHHI) model for Africa: A report from the stakeholders meeting held in Lambaréné, Gabon, November 10–11, 2019

Abstract: Background Hookworm is a major contributor to worldwide disease burden with over 230 million people infected. It has been identified as one of the Neglected Tropical Diseases that can be controlled and even eliminated through mass drug administration and other effective interventions. Mathematical models have shown that hookworm can only be eliminated via a vaccine. Controlled Hookworm Human Infection (CHHI) models can facilitate rapid development of vaccines and drugs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…This process of engagement was recommended by Ugandan stakeholders in preparation for CHI-S (Elliott et al, 2018 ). Similarly, other CHI studies have also recommended and conducted community engagements with the target communities in disease-endemic countries such as Zambia (Kunda-Ng’andu et al, 2021 ), Vietnam (Kestelyn et al, 2019 ), India (Vaz et al, 2019 , 2020 ), Malawi (Kapumba et al, 2020 ), Kenya (Njue et al, 2018 ), and Gabon (Alabi et al, 2021 ). The studies showed that participants are able to understand the processes involved during a CHI.…”
Section: Discussionmentioning
confidence: 99%
“…This process of engagement was recommended by Ugandan stakeholders in preparation for CHI-S (Elliott et al, 2018 ). Similarly, other CHI studies have also recommended and conducted community engagements with the target communities in disease-endemic countries such as Zambia (Kunda-Ng’andu et al, 2021 ), Vietnam (Kestelyn et al, 2019 ), India (Vaz et al, 2019 , 2020 ), Malawi (Kapumba et al, 2020 ), Kenya (Njue et al, 2018 ), and Gabon (Alabi et al, 2021 ). The studies showed that participants are able to understand the processes involved during a CHI.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, organoids could overcome barriers in research focused on aspects of the infection that are host-restricted and cannot be replicated using an animal model due to significant interspecies differences (Duque-Correa et al, 2020a). This is particularly relevant for human GI nematodes that do not have any system for investigation besides controlled infections that have limited experimental read outs (Diemert et al, 2018;Alabi et al, 2021;Pritchard et al, 2021). The lack of models for human infective nematodes has driven the use of nematode parasites of rodents or other mammals, which have similar life cycles or induce comparable pathogenesis as human infective species.…”
Section: Organoids As Systems To Recreate the Life Cycles Of Gi Nemat...mentioning
confidence: 99%
“…The recreation of the life cycle of human and livestock GI nematodes in vitro using organoids could revolutionise the helminthology field by allowing not only a better understanding of their pathogenesis but also of their "beneficial" effects on the control of inflammation. Organoids could become a key tool to interpret the results of controlled hookworm and whipworm human infections (Diemert et al, 2018;Alabi et al, 2021;Chapman et al, 2021) and on the identification of parasite ES molecules produced by specific larval/adult stages that mediate anti-inflammatory actions of GI nematodes (Maizels et al, 2018). Moreover, organoids could also have a great impact on the development of new anthelmintics and on studies of anthelmintic resistance by allowing investigations on the effects of drugs on the different life cycle stages.…”
Section: Organoids As Systems To Recreate the Life Cycles Of Gi Nemat...mentioning
confidence: 99%